2003
DOI: 10.1055/s-2003-38198
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Changes in c-Fos Protein Levels in Skeletal Muscle of Trained and Untrained Rats

Abstract: We investigated the effect of an acute bout of endurance exercise on c-Fos protein levels in the extensor digitorum longus muscle of trained and untrained rats. Fifty rats were equally divided into a trained and an untrained group. Rats of the trained group ran on a treadmill 45 min/day for 5 days. On the sixth day, 5 rats were killed without exercise, while the remaining 20 ran as above and were killed 0, 3, 6, and 12 h post-exercise (5 rats at each time point). In the untrained group, 5 rats were killed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Fos, Fosb, and Atf3 are immediate early genes that respond to an array of stressors and are components of activator protein 1 transcription factor, a diverse group of heterodimers composed of FOS, JUN, and ATF proteins that have been implicated in a multitude of processes including cell proliferation, apoptosis, and mitochondrial gene expression (9,46). Skeletal muscle expression of FOS and ATF3 are transiently upregulated following exercise and are postulated to mediate some of the beneficial effects of exercise, including increased expression of mitochondrial proteins and antioxidants and blunted expression of inflammation-related genes, respectively (13,38). Furthermore, one of the MetaCore pathway maps uniquely upregulated in the HFD ϩ DHA group compared with the control was the sirtuin 6 pathway, which responds to oxidative stress and plays a role in maintaining DNA integrity (4).…”
Section: E468mentioning
confidence: 99%
“…Fos, Fosb, and Atf3 are immediate early genes that respond to an array of stressors and are components of activator protein 1 transcription factor, a diverse group of heterodimers composed of FOS, JUN, and ATF proteins that have been implicated in a multitude of processes including cell proliferation, apoptosis, and mitochondrial gene expression (9,46). Skeletal muscle expression of FOS and ATF3 are transiently upregulated following exercise and are postulated to mediate some of the beneficial effects of exercise, including increased expression of mitochondrial proteins and antioxidants and blunted expression of inflammation-related genes, respectively (13,38). Furthermore, one of the MetaCore pathway maps uniquely upregulated in the HFD ϩ DHA group compared with the control was the sirtuin 6 pathway, which responds to oxidative stress and plays a role in maintaining DNA integrity (4).…”
Section: E468mentioning
confidence: 99%
“…The major advantage of rats over mice is the greater tissue sample size and the larger blood volume that allows measurement of a complete set of blood biomarkers. Rats have been used to address diverse research questions in the exercise physiology field including physical performance (Veskoukis et al 2008;Booth and Laye 2009), metabolism (Nikolaidis et al 2004;Brooks 2009), fatigue (Allen et al 2008;Kyparos et al 2012), muscle atrophy (Fitts et al 2001;Kyparos et al 2005), gene expression, and signaling pathways (Nikolaidis et al 2003;R€ ockl et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise possesses remarkable eff ect on adult skeletal muscle mass, function and metabolism, the magnitude and direction aff ected by a variety of factors including the mode, intensity, and duration of the exercise performed, as well as the training state of the individual. It has been demonstrated that an acute bout of endurance exercise can increase skeletal muscle protein levels [ 46 ] , strength training may induce muscle hypertrophy [ 25 ] , and high-intensity eccentric exercise may induce muscle injury [ 35 ] . However, few studies have addressed the eff ects of overtraining on skeletal muscle, especially the mechanisms involved.…”
mentioning
confidence: 99%